SYSTEMATIC RELATIONSHIPS WITHIN CHIRODERMA (CHIROPTERA, PHYLLOSTOMIDAE) BASED ON CYTOCHROME-B SEQUENCE VARIATION - Baker, R. J.; Taddei, V. A.; Hudgeons, J. L.; Vandenbussche, R. A. (Alliance Communications Group Division Allen Press, 1994)
The Neotropical bat genus Chiroderma consists of five recognized species. This study uses DNA-sequence variation of the mitochondrial cytochrome b gene to infer the phylogenetic relationships within Chiroderma. Phylogenetic relationships deduced from these data by parsimony analyses resulted in the discovery of a single most-parsimonious tree with C. salvini diverging basal to the other four species of Chiroderma and sister-group relationships of C. villosum with C. improvisum and C. trinitatum with C. doriae. This is a relatively young group of species with approximate times of divergence ranging from 1.6 million years before present (mya) for the divergence of C. doriae from C. trinitatum to 4.6 mya for the divergence of C. salvini from the other four species of Chiroderma.
Keywords: MOLECULAR PHYLOGENETICS; CYTOCHROME-B; CHIRODERMA; DNA SEQUENCE